Increasing Human Literacy for Generation Z Through Learning to Use Technology in Indonesia - Riza M. Yunus (GoAcademica Research & Publishing, 2021)
The use of technology in the learning process is quite commonly used today, such as online learning. To be able to carry out this online learning, it is necessary to have three literacy skills, namely technological literacy, data literacy, and human literacy. Generation Z, currently in the world of education, uses various learning methods, such as online learning. This study aims to see how the application in the use of technology can improve human literacy skills for Gen Z in Indonesia. This research will be conducted using a qualitative SWOT analysis method. This study found that there are still difficulties in increasing human literacy for Gen Z because of their characteristics, most of which are difficult to communicate directly and instantly. Then the characteristics of most of them also choose to live in the present, their attention span is still short, and their ability to validate information is relatively low.